ANÁLISE DA EVOLUÇÃO DOS PREÇOS DA CESTA BÁSICA DE SANTA ROSA, RS - Dall’Alba, Maicon; Muenchen, José Valdemir; Zamberlan, Luciano; Sparemberger, Ariosto (Salão do Conhecimento, 2017)
Projeto de pesquisa realizado no curso de Administração da Unijuí